2018
DOI: 10.5115/acb.2018.51.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effects of Moringa on cuprizone-induced memory decline in rat model of multiple sclerosis

Abstract: Cuprizone is a neurotoxin with copper-chelating ability used in animal model of multiple sclerosis in which oxidative stress has been documented as one of the cascade in the pathogenesis. Moringa oleifera is a phytomedicinal plant with antioxidant and neuroprotective properties. This study aimed at evaluating the ameliorative capability of M. oleifera in cuprizone-induced behavioral and histopathological alterations in the prefrontal cortex and hippocampus of Wistar rats. Four groups of rats were treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 32 publications
(38 reference statements)
0
20
0
Order By: Relevance
“…In addition, CPZ diet showed neurotoxic effects evidenced by chromatolysis, abnormal Nissl granules, hyperchromatic nuclei and vacuolated neurons in the prefrontal cortex that is also ameliorated by DAP treatment. Previous studies have demonstrated that CPZ administration resulted in prefrontal cortex and hippocampus damage inducing pyknosis, central chromatolysis and cellular fragmentations [43,44]. The changes in the cellular morphology may be linked to the elevation of oxidative stress mediators such as superoxide anion and nitrite ad that can damage neurons and apoptosis [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CPZ diet showed neurotoxic effects evidenced by chromatolysis, abnormal Nissl granules, hyperchromatic nuclei and vacuolated neurons in the prefrontal cortex that is also ameliorated by DAP treatment. Previous studies have demonstrated that CPZ administration resulted in prefrontal cortex and hippocampus damage inducing pyknosis, central chromatolysis and cellular fragmentations [43,44]. The changes in the cellular morphology may be linked to the elevation of oxidative stress mediators such as superoxide anion and nitrite ad that can damage neurons and apoptosis [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the MWM method was adopted to evaluate the cognitive-enhancing effects of the aqueous and stem bark extracts of L. eriocalyx in scopolamine-induced cognitively impaired mice model. This technique has been broadly utilized to screen drug agents proposed for dementia and symptoms of cognitive impairment [ 42 46 ]. The MWM task is useful in assessing spatial learning and memory in laboratory animals and humans.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, this study further investigated the neurotoxic tendencies of permethrin on the antioxidant status of brain regions using SOD, GPx and CAT as biomarkers. These enzymes are in the frontline of antioxidant defense system [ 42 , 43 ]. Findings showed that permethrin affected the activities of these enzymes in a dose-dependent pattern across the three brain regions, such that the higher the dose of permethrin, the lower the enzyme activities.…”
Section: Discussionmentioning
confidence: 99%